Effects of Aging on Formalin-Induced Pain Behavior and Analgesic Activity of Gabapentin in C57BL/6 Mice - Scuteri, Damiana; Berliocchi, Laura; Rombolà, Laura; Morrone, Luigi Antonio; Tonin, Paolo; Bagetta, Giacinto; Corasaniti, Maria Tiziana (Frontiers in Pharmacology, 2020)
Improved living conditions have induced an increase of lifespan often accompanied by comorbidities, responsible for pain, and by cognitive impairment and dementia, impairing communication capabilities. In most cases, the elderly do not receive pain relief because of underdiagnosis and of aging-induced changes of systems affecting nociceptive response. Unrelieved pain is involved in the development of behavioral symptoms, as agitation, representing a difficult challenge in this fragile population. Aged C57BL/6 mice and amyloid precursor protein (APP) mice display behavioral disturbances that mimic behavioral and psychological symptoms of dementia (BPSD). Therefore, this original study focuses on the influence of aging on nociception to provide insight into the occurrence of BPSD. We have investigated how aging can affect nociception after formalin administration and gabapentin effect in C57BL/6 mice, since it represents one of the treatments of choice for chronic neuropathic pain. Based on our results, changes of nociceptive behavior in response to an algogen stimulus occur during aging. Formalin-induced behavioral pattern in older C57BL/6 mice presents a temporal shift and an increase in the peak amplitudes. Our data show that the effectiveness of gabapentin is influenced by the age of the animal; though preliminary, the latter provide evidence upon which formalin test induced long-lasting mechanical allodynia might be a reliable as rapid and viable persistent pain model. The disclosed differences in effectiveness of gabapentin according to age can form the rational basis to deepen the study of pain treatment in the elderly.